ANALYSIS OF THE INFLUENCE OF MARKETING MIX ON CUSTOMER LOYALTY IN THE SOCIETY 5.0 ERA - Demak Claudia Yosephine Simanjuntak; Wenny Anggeresia Ginting (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to examine and analyze the influence of the marketing mix on customer loyalty in the era of society 5.0. This research method is survey research by distributing questionnaires to customers. The population in this study were all customers of Grab Food Medan. The sample in this study was 100 people with a sampling technique that is random sampling. The sample criteria in this study are customers who have purchased using Grab Food three times. In this study, the type of data used is primary data, namely data from questionnaires about the influence of the marketing mix on customer loyalty. Data collection techniques are questionnaires, questionnaires and interviews. The variable in this study is the marketing mix which consists of product, price, promotion and place as the independent variable and customer loyalty as the dependent variable. The questionnaire used has been tested for validity and reliability. The data analysis technique used in this research is descriptive analysis and regression analysis. Descriptive analysis to determine the characteristics of respondents and regression analysis to examine the effect of the marketing mix on customer loyalty. The results of this study indicate that the marketing mix, namely product, price, promotion and place, has a positive and significant effect on customer loyalty in the era of society 5.